2008
DOI: 10.1038/nature07180
|View full text |Cite
|
Sign up to set email alerts
|

Earliest date for milk use in the Near East and southeastern Europe linked to cattle herding

Abstract: The domestication of cattle, sheep and goats had already taken place in the Near East by the eighth millennium bc. Although there would have been considerable economic and nutritional gains from using these animals for their milk and other products from living animals-that is, traction and wool-the first clear evidence for these appears much later, from the late fifth and fourth millennia bc. Hence, the timing and region in which milking was first practised remain unknown. Organic residues preserved in archaeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
329
1
22

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 532 publications
(387 citation statements)
references
References 18 publications
20
329
1
22
Order By: Relevance
“…29,30 Organic residues preserved in archaeological pottery have provided the earliest direct evidence for the use of milk in the seventh millennium in the Near East. 27 But, although milking was particularly important in NorthWestern Anatolia, the data point to regional differences linked with conditions more favourable to cattle husbandry, compared with other regions, where milk usage was less important. 27 Thus, although some researchers suggest that dairy products would have been exploited rapidly after animal domestication, 31 others have suggested that early domestication was predominantly for meat and hides, postulating a 'secondary products revolution' 2000-4000 years after the first domestication of cattle, sheep and goats in the Near East and Europe.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…29,30 Organic residues preserved in archaeological pottery have provided the earliest direct evidence for the use of milk in the seventh millennium in the Near East. 27 But, although milking was particularly important in NorthWestern Anatolia, the data point to regional differences linked with conditions more favourable to cattle husbandry, compared with other regions, where milk usage was less important. 27 Thus, although some researchers suggest that dairy products would have been exploited rapidly after animal domestication, 31 others have suggested that early domestication was predominantly for meat and hides, postulating a 'secondary products revolution' 2000-4000 years after the first domestication of cattle, sheep and goats in the Near East and Europe.…”
Section: Discussionmentioning
confidence: 92%
“…27 But, although milking was particularly important in NorthWestern Anatolia, the data point to regional differences linked with conditions more favourable to cattle husbandry, compared with other regions, where milk usage was less important. 27 Thus, although some researchers suggest that dairy products would have been exploited rapidly after animal domestication, 31 others have suggested that early domestication was predominantly for meat and hides, postulating a 'secondary products revolution' 2000-4000 years after the first domestication of cattle, sheep and goats in the Near East and Europe. 32 In Europe, it is estimated that agriculture has been introduced from 8000 to 6000 YBP, 33,34 and specifically for the Basque Country around 7000 YBP.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Most of the assemblages investigated comprised globular or bowl shape 'cooking' vessels, an interpretation supported by the finding of ruminant and porcine animal fats in significant numbers of vessels. No beeswax resi dues were detected during the intensive investigations of > 380 vessels from the Levant, although only 34 residues were detected 20 . Moving into eastern Anatolia, the site of Çayönü Tepesi revealed two beeswax residues from 83 vessels from the seventh millennium including an exceptionally well preserved residue containing all the biomarkers of beeswax (Fig.…”
mentioning
confidence: 97%
“…The free n alkanols, dominated by C 30 and C 32 homologues, do not occur in fresh beeswax but are a feature of aged wax, due to hydrolysis of the wax esters. The high abundance of C 18:0 fatty acid suggests mixing with mammalian animal fat, the latter being common in other sherds in the assemblage 20 . The second sherd from this site contained a lower concentration of beeswax but all the bio markers were clearly evident.…”
mentioning
confidence: 99%